The pro apoptotic effect of brittle Star dichloromethane extract on B16F10 melanoma cell line - Baharara, Javad; Amini, Elaheh; Nikdel, Najme; Afzali, Mahbubeh (Archives of Advances in Biosciences, 2015)
Cancer is the second important reason of mortality in the world. In this regard melanoma was accounted as the most aggressive type of coetaneous cancer. Among drug extracted from natural products from marine organisms have been focused investigations related to chemotherapeutic agents derived from echinoderms such as sea cucumbers and starfish. In the present study, cytotoxic and apoptosis inducing potential of Persian Gulf Brittle Stars dichloromethane extract were evaluated against melanoma cancers. In this study, anti-proliferative effect of brittle stars Dichloromethane extract on B16F10 melanoma cells examined by MTT assay and morphological characterization and death inducing effect of Annexin-PI and PI flow cytometry. The data analysis was performed by SPSS software and p<0/05 were considered significant. The dichloromethane extract of brittle star revealed significant cytotoxic effect on B16F10 melanoma cells with IC50= 31 µg/ml which is stronger than inhibitory effect of methanol extract on melanoma cell growth. In addition, brittle star dichloromethane extract recruited apoptotic pathway in the response of 31 µg/ml treatment. This study showed that certain concentrations of dichloromethane brittle stars possess cytotoxic activity that can be used as an anticancer agent used in clinical trial due to cell growth inhibition and apoptosis induction which offer therapeutic investigations of dichloromethane brittle star extract as complementary for melanoma treatment and prevention.